Synthesis of polyfluoroacrylate emulsion and coatings for hydrophobic and icephobic applications - Barman, Tamal (2020)
Low surface energy polymeric materials always attract great interest due to their effective non-stick feature when contacting with other materials. Surface roughness in addition to the low surface energy elevates the hydrophobicity of the surface and makes it superhydrophobic. Ice adhesion and formation is one of the major problems for many industries including aerospace, wind energy and transportation. Superhydrophobic surfaces are potentially used for icephobic applications. In the present work, hydrophobic polyfluoroacrylates (PFAs) were synthesized using styrene, acrylic acid, and heptafluorobutyl acrylate via radical polymerization method. The synthesized PFA emulsions had a relatively low curing temperature (e.g. 80 °C), and different molar ratios of heptafluorobutyl acrylate were used to vary the fluorine content in the polymer. The polymerization is a random co-polymerization process and hence the exact arrangement of the groups cannot be predicted. X-ray photoelectron spectroscopy revealed that the maximum fluorine content in the PFA emulsion can reach up to 34 Wt%. Average ultimate tensile strength of the synthesized polyfluoroacrylate was measured at ~37 MPa which is comparable to that of PTFE ~35 MPa. From chemical analysis by Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and nuclear magnetic resonance, it was found that the synthesized PFA emulsion exhibited co-polymer structure consisting of the three monomer units. For the study of surface morphology, three different processes were used: anodisation, chemical etching and Cu-nanoparticle deposition. From scanning electron microscopy (SEM) images and 3D profilometer measurement, it had been found that anodistion and chemical etching produced micrometer range surface roughness and Cu-nanoparticle deposited surfaces had a nanometer range surface roughness. Below 10 °C, anodisation gave relatively uniform surface roughness in the range of 1-2 µm, and with the increase in temperature the surface roughness reached beyond 5 µm. When the aluminium surface was etched with a mixture of hydrochloric acid (HCl) and hydrogen peroxide (H2O2), average surface roughness of 1.5-1.8 µm was obtained. When Cu-nanoparticles were deposited, surface roughness reduced to nanometer range of 20-50 nm, but the Cu-nanoparticles tended to agglomerate and hence non uniform surface roughness was obtained. PFA was deposited on the modified surface by mainly spin coating process. The surface roughness of the coating decreased after the deposition of the PFA emulsion. Hydrophobicity of the coatings was evaluated using water contact angle (WCA) and contact angle hysteresis (CAH). For anodised samples, the WCA and CAH values gradually increased with increasing surface roughness, indicating the decrease in hydrophobicity. Chemical etched surfaces had surface roughness in the range of 1.5 – 2 µm and hence hydrophobicity was almost maintained throughout. For Cu-nanoparticle deposited samples, hydrophobicity was also maintained, evidenced from the average WCA at ~140° and CAH below 10°. The coating erosion test indicated that the lowest coating adhesion was obtained on the nanoparticle deposited surfaces, as the nanoparticles were loosely bound on the substrate surface. Chemically etched hydrophobic surfaces showed the highest erosion resistance. Ice adhesion strength and de-icing tests showed that anodised samples had the highest ice adhesion as compared to chemically etched and nanoparticle deposited hydrophobic surfaces as the ice anchored in the large cavities on the anodised surfaces. Anodisation also formed a thin layer of Al2O3 on the surface which was non conductive and hence de-icing time was higher. For Cu nanoparticle deposited surfaces the de-icing time was least as the Cu-nanoparticle layer was thermally conductive, and hence when heat was applied on the coating, it can easily remove the ice and increase the efficiency of the coating.